PREVALENCE AND ANTIMICROBIAL RESISTANCE IN ENTEROCOCCUS SPECIES - OHRI, SANIYA; SINGH, KANWARDEEP; SIDHU, SHAILPREET KAUR; OBEROI, LOVEENA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The study was conducted to determine the prevalence of vancomycin-resistant Enterococci (VRE) isolated from various clinical samples received from the indoor patients of all age groups admitted in Government Medical College and Hospital, Amritsar. Methods: A prospective cross-sectional study was conducted in the Department of Microbiology, Government Medical College, Amritsar, for a period of 4 years (July 1, 2018–June 30, 2022). All the samples (pus, urine, blood, body fluids, sputum, etc.) received from the indoor patients of all age groups admitted in Government Medical College and Hospital, Amritsar, were included in the study. Results: During the study period of 4 years, among the culture positive samples, 1815 (6.62%) isolates were identified as Enterococcus species. Among 1815 isolates, 1089 isolates were Enterococcus faecalis (60%) and 726 were Enterococcus faecium (40%). Both E. faecalis and E. faecium isolates showed the maximum resistance to ciprofloxacin while linezolid, teicoplanin, and quinupristin/dalfopristin showed the maximum sensitivity. Conclusion: Our study reports the prevalence of Enterococci isolates as well of VRE isolates. To reduce the VRE prevalence worldwide, appropriate use of antibiotics according to antimicrobial susceptibility testing should be encouraged. Efforts should be made to reduce the transmission of VRE isolates.